Engineering of Dakwah Study - Kohar, Wakidul (Universitas Islam Negeri Imam Bonjol Padang, 2005)
Dakwah term hasn '1 defined explicitly yet by Messenger of Allah, wether from his attitudes or activities, even he has told that he was sent lo the earth as an educator da't and conselor. It is different from other terms like shalat, zakat, puasa and haft that have been concluded as the sacre things m Islamic activities Becuuse of that, dakwah presents multi interpreiable space to every bocy in understanding it Scholars have freedom in referencing theirs dakwah activilies warious definillon of dakwah. Dakwah Sctence ontologically jusi limted it self on empiricall and thonght apects Other aspects beyond Inuman capability are Out of this study to caused